Toxic epidermal necrolysis and Stevens‐Johnson syndrome after COVID‐19 infection and vaccination - Zou, Henry; Daveluy, Steven (Australasian journal of dermatology, 2023)
Stevens‐Johnson Syndrome (SJS) is a rare but severe skin reaction characterized by blistering and peeling of the skin and ulcerations of mucous membranes; toxic epidermal necrolysis (TEN) is a subset of SJS characterized by the involvement of >30% of the skin. Though previously associated with drugs and infections, discussions on the association between TEN/SJS and COVID‐19 have been limited. We present a review of TEN/SJS after COVID‐19 infection and vaccination. Literature searches were conducted on PubMed and Google Scholar from 2019 to 8/2022. Thirty‐eight articles were selected based on subject relevance, and references within selected articles were also screened for relevance. As of 8/2022, there have been 34 published cases of TEN, SJS, and SJS‐TEN overlap after COVID‐19 infection and vaccination, including 12 cases after vaccination and 22 cases after infection. Multiple authors hypothesize that virotopes or excipients in COVID‐19 vaccines can activate T‐cells or cytokines to induce TEN/SJS. Meanwhile, some hypothesize that COVID‐19 infection induces immune activation that can trigger TEN/SJS or increase susceptibility to drug‐induced TEN/SJS. Treatments for post‐infection and post‐vaccination TEN/SJS vary significantly. We recommend remaining vigilant for this rare and severe potential complication.